Post Flood Disaster Management Practices with Collaborative Governance in Indonesia - Dedeh Maryani; Achmad Suhawi; Ika Ahyani Kurniawati; Isnaldi Muhammad Dini (Sean Institute, 2025)
This research is motivated by the fact that the major floods and landslides that struck Aceh, North Sumatra, and West Sumatra at the end of 2025 caused multidimensional impacts, including loss of life, mass displacement, and damage to infrastructure and ecosystems. The complexity of post-disaster management demands cross-sector collaborative governance in accordance with the mandate of Law No. 24 of 2007. This study aims to analyze the urgency and design of multi-stakeholder collaboration from a Public Administration perspective, grounded in Collaborative Governance theory, Collaborative Governance Regimes, and the Pentahelix model. The research employs a qualitative-descriptive approach through literature review and policy analysis. Data are drawn from regulations, theoretical literature, reports from BNPB/BPBD, and national media publications. Analysis is conducted by mapping theoretical frameworks to field findings, identifying implementation gaps, and synthesizing policy recommendations. The results indicate that post-disaster management in Sumatra faces obstacles such as regional isolation, disruptions to electricity and telecommunications networks, limited capacity of BPBD, and ecological vulnerability in upstream areas. The application of trust-building principles, small wins, and CGR-based collaborative regimes can strengthen cross-provincial coordination. The Pentahelix model serves as a practical architecture to orchestrate the roles of government, communities, academia, the private sector, and the media in restoring basic services, rehabilitating infrastructure, and reducing recurrent risks. Collaborative governance that integrates the Ansell & Gash framework, the Emerson–Nabatchi CGR, and the Pentahelix model is key to effective post-disaster flood management in Sumatra. Policy recommendations include establishing cross-provincial Collaborative Command Posts, adopting operational small wins, integrating academic studies into technical decision-making, strengthening a unified disaster data system, and considering national disaster status in accordance with the indicators set out in Law No. 24 of 2007